Peran Pemerintahan Mukim Dalam Upaya Meningkatkan Pembangunan Desa Di Kecamatan Terangun, Kabupaten Gayo Lues - khaidir ali; Winda S Meliala; Corry Novrica AP Sinaga (Jurnal Intervensi Sosial dan Pembangunan, 2023)
The purpose of this study was to determine the role of the mukim government in efforts to improve village development in Mukim Want Jaya, Terangun District, Gayo Lues Regency. The method used in this research is descriptive qualitative where this method is a type of research method that seeks to describe and interpret objects as they are. The results of this study indicate that there is work order and control in achieving the goals carried out by the leadership in implementing public policies where the existing mukim government has carried out its orders and supervision. interaction between government and society. decisions in work procedures are where there are procedures and decisions made based on Qanun. there are actions taken by the head of the mukim in carrying out his duties and obligations such as his goal in carrying out development. However, in practice there are still some obstacles.Keywords: Role, Mukim Government, Village Development.